Pemanfaatan Aplikasi Cam Multimedia pada Teknik Photo Editing untuk UMKM Kelurahan Palmerah, DKI Jakarta - Wawan Gunawan; Yudo Devianto; Saruni Dwiasnati; Herry Derajad Wijaya (Universitas Mathla'ul Anwar Banten, 2021)
UTILIZATION OF MULTIMEDIA CAM APPLICATION IN PHOTO EDITING TECHNIQUES FOR MSMES IN PALMERAH KELURAHAN, DKI JAKARTA. This Community Service that we undertake together is excellent for assisting MSMEs increase their knowledge and abilities about marketing a product that uses digital technology by using a gadget called a multimedia cam to do photo editing so that the product looks appealing. Buyers want to see the goods in greater depth. So that MSMEs can rise and grow their businesses in the face of a pandemic, expanding their market, raising awareness, and increasing sales and profits. This service plan is being implemented in Palmerah Village with the goal of increasing the number of MSMEs registered in the village to 160 by 2020. MSMEs registered in Palmerah Village in 2020 are interested in a variety of business disciplines. It can be noted that 74% of respondents thought PKM activities in shooting training were very good; additionally, 36% of respondents thought future events were very good, and 35% desired the activity to be done again with current material and offline.